Contemporary Business Issues in Malaysia: How does this “Tiger Cub” feel today? - Salamzadeh, Yashar; Radovic Markovic, Mirjana; Khajeheian, Datis (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2s (2019): Special Issue: Contemporary Business Issues in Malaysia: How does this “Tiger Cub” feel today?, 2019)
Malaysia has played an important role in the economy of South-East Asia in last decades and is among the most successful economies in developing countries of the region. Of course, there are some concerns on the speed of growth, change and economic share of competing economies in this vital economic region. Malaysia has started new initiatives to speed up the process of growth both in economic and human capital dimensions. This is why there is a need to know more about the current status of the business ecosystem of this country. Getting a better and more comprehensive view of the business ecosystem in Malaysia guided us to a broader scope for this special issue. In this special issue, all researchers are invited to submit their research articles in different aspects of Malaysia’s business environment mainly investigating cases in Malaysia. Research paper  Keywords: Entrepreneurship; New Venture Creation; Psychology; Competencies; E-Commerce Reference to this paper should be made as follows: Salamzadeh, Y., Radovic Markovic, M., & Khajeheian, D. (2019). Contemporary Business Issues in Malaysia: How does this “Tiger Cub” feel today?, Journal of Entrepreneurship, Business and Economics , 7 (2s), 1–6.